Analysis of Potential Hazards in the Palm Oil Processing Process at PT. Karya Tanah Subur Using Job Safety Analysis (JSA) - Muhammad David; Heri Tri Irawan (Jurnal Inotera, 2023)
PT. Karya Tanah Subur (KTS) is a palm oil processing industry located on Jalan Gemmpang-Tutut, Padang Sikabu Village, Kawai XVI District, West Aceh District. Based on the results of observations and interviews conducted with the person in charge of the factory, it is known that there are potential hazards that occur during the production process. The potential hazards that occur cannot be separated from various risks in the work environment, as well as negligence and also non-compliance by workers in using PPE. The purpose of this research is to identify the potential hazards at the Loading Ramp, Sterilizer, and Thresher stations and then assess the risk level of these potential hazards and determine control measures for these risks. The method used in this research is Job Safety Analysis (JSA). The results of the analysis revealed that the potential hazards in the 3 areas studied were the Ramp Loading, Sterilizer, and Thresher stations. The potential hazards found in the Ramp Loading area were being pinned by the tailgate of the FFB transport truck, being crushed and punctured by FFB thorns, falling into a pile of FFB, being stabbed by a gancu. . Potential hazards at the Sterilizer Station include exposure to hot steam, electric shock, heat at the end of the lorry, being injured by capstand ropes and slipping due to slippery floors. The potential hazards at the Thresher station include being exposed to the heat of the lorry when it is unable to attach the rope that holds the crane, falling from the workplace, being crushed by fruit that has been boiled in heat. The highest potential hazards are at the Sterilizer station, where workers' hands are injured by capstand ropes and the slippery floor causes workers to slip, and at Thersher stations, where boiled fruit is crushed. Control efforts that can be proposed are to hold internal outreach to company workers which discuss risks in the workplace as well as discussions about occupational health and safety so that workers always use complete PPE in the workplace.